Assessments in occupational therapy mental health : an integrative approach - Hemphill, Barbara J.; Urish, Christine, 1965- (Thorofare, NJ : SLACK Incorporated, 2020)
'Assessments in Occupational Therapy Mental Health: An Integrative Approach, Fourth Edition is a unique compilation of mental health assessments that are taught in occupational therapy academic programs and used in clinical practice. This highly anticipated Fourth Edition provides the occupational therapy student and educator with knowledge about the evaluation process, assessments that are current and accurate, and how to generate research for developing assessment tools. Assessments in Occupational Therapy Mental Health, Fourth Edition by Drs. Barbara J. Hemphill and Christine K. Urish, along with more than 30 world-renowned contributors, includes 15 new assessments, along with updates to 9 assessments from the previous editions. Also incorporated throughout the text is the AOTA's Occupational Therapy Practice Framework, Third Edition. While introducing new assessments and updated information, Assessments in Occupational Therapy Mental Health: An Integrative Approach, Fourth Edition is ideal for occupational therapy faculty, students, practitioners, as well as nurses, psychologists, and social workers'--
Includes bibliographical references and index.
Description based on onine resource; title from resource home page (EBSCOhost, viewed April 19, 2021).
WorldCat record variable field(s) change: 650
Keywords: Occupational therapy; Mentally ill -- Rehabilitation; Psychology, Pathological -- Diagnosis; Needs assessment; Occupational Therapy -- methods; Persons with Mental Disabilities -- rehabilitation; Needs Assessment; Occupational Therapy; Mentally ill -- Rehabilitation; Occupational therapy; Psychology, Pathological -- Diagnosis; Electronic books; Electronic books